The construction of learner identity in a global Englishes era: A self-reflection - M. Faruq Ubaidillah (Universitas Jambi, Magister Program of English Education Department, 2022)
This paper is geared by my perceptual understanding on insights of teaching English as an international language (TEIL). It firstly departs from my conservative belief that the best English to teach is British and American. Apparently, these English(es), shaped by the linguistic imperialism, are the ‘only perfect’ language in the international communication. However, my mind has altered to be paradoxically blessed with the knowledge I gain from reading studies on World Englishes(WEs) and English as an international language (EIL) issues extensively, for instance, works by Kachru (1985, 2005); Zacharias (2003); Floris (2013); Mukminatien (2012); Renandya (2013); and Kirpatrick (2007). Their works on both EIL and WEs have broadened my narrow-minded perspectives on the issues. For this tenet, the paper reflects on my identity construction as a language learner which has been anchored amidst the issues of incorporating WEs in English education curriculum. It seems problematic, however, to realize this idea since the curriculum of English language teaching in Indonesia excludes this issue. It is for this purpose then that the present paper highlights the issue of WEs in the teaching of English and my identity construction as a language learner. Suggestions for inserting WEs in teaching English is also discussed at the end of this paper.